The Phenomenon of Taxpayer Compliance in Paying PBB-P2 in Pitu District, Ngawi Regency - Hidayah, Vebby Noer; Mujiyati, Mujiyati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research aims to analyze the phenomenon of taxpayer compliance in paying PBB-P2 in Pitu District, Ngawi Regency. The population in this study is the PBB-P2 mandatory in the Pitu sub-district area, Ngawi Regency with a number of 20,427. The sample size was determined by using the Slovin formula and obtaining a sample of 104 respondents. All data was collected using a questionnaire and then processed using multiple linear regression analysis techniques with the help of SPSS software. The results of the analysis show that PBB-P2 Tax Sanctions, PBB-P2 NJOP, and taxpayer education level have a significant influence on taxpayer compliance. However, taxpayer awareness, tax knowledge, and tax authorities services do not have a significant effect on taxpayer compliance. Furthermore, the regression model shows that together, taxpayer awareness, tax knowledge, tax sanctions, tax service, NJOP, and taxpayer education level significantly influence rural and urban land and building tax compliance (PBB-P2).